The single market and the geographical diversification of leading firms in the EU - Frank G. Barry; Stephen Pavelin (University College Dublin, Department of Economics, 2003)
Geographical diversification describes the degree to which a firm's operations in a particular industry are dispersed across countries. This paper presents evidence on the geographical diversification within the EU of the 290-odd largest manufacturing firms in Europe. We also explore how geographical diversification changed with the introduction of the Single Market. We highlight differences between firms' home and foreign operations and study the variation across sectors and across EU countries. Ireland, which began its rapid FDI-fuelled convergence on average EU living standards over our data period, emerges as a special case and receives particular attention.
hdl:10197/1327
Keywords: F15; F23; O52; 330; Single Market; Geographical Diversification; FDI; Multinational Corporations; EU-Binnenmarkt; Multinationales Unternehmen; Betrieblicher Standort; Regionales Cluster; EU-Staaten